Cardiac parasympathetic reactivation after a high-intensity intermittent effort in water polo players: impact of swimming endurance performance status - Brisola, Gabriel Motta Pinheiro; Gomes, Vinicius Garcia; Dutra, Yago Medeiros [UNESP]; Botonis, Petros G.; Zagatto, Alessandro Moura [UNESP] (Springer Nature, 2024)
Purpose: The purpose of the study was to compare early cardiac parasympathetic reactivation measured through heart rate variability (HRV) metrics after a high-intensity intermittent effort in water polo players classified as higher (HSEP; n = 10) or lower swimming endurance performance status (LSEP; n = 9). Methods: Nineteen young male water polo players were classified into HSEP and LSEP according to 400 m crawl swimming test. The HRV (heart rate [HR] and the natural log of the root-mean-square difference of successive normal RR intervals [LnrMSSD]) was assessed at baseline (resting) and immediately after a high-intensity intermittent effort (14×25 m all-out front crawl swim) for 3 min. Results: The baseline LnrMSSD was not statistically different between the groups (HSEP = 4.0 ± 0.4 a.u. and LSEP = 3.8 ± 0.4 a.u., Effect Size [ES] = 0.6). Further, no significant interaction effect was found for HRV metrics post-exercise. Only moderate ES were found in favor of HSEP for LnrMSSD at 0–30 s (HSEP = 1.5 ± 0.4 a.u. and LSEP = 1.2 ± 0.4 a.u., ES = 0.6) and 30–60 s recovery time (HSEP = 1.5 ± 0.4 and LSEP = 1.2 ± 0.4, ES = 0.7), and moderate-to-large ES in favor of HSEP group for HR recovery from 60 to 90 s (HSEP = 130 ± 10 bpm and LSEP = 137 ± 8 bpm, ES = − 0.8) to 150-180 s (HSEP = 111 ± 8 bpm and LSEP = 117 ± 8 bpm, ES = − 0.6) recovery time. Conclusion: The present findings showed that there was no significant difference for HRV metrics between HSEP and LSEP at baseline and after exercise. The ES analysis indicates the need of further studies to confirm whether the endurance performance status has any impact on cardiac parasympathetic reactivation of water polo players.
Keywords: Aerobic fitness; Fatigue; Heart rate variability; Recovery; Swimming; Team sport